RESPON KOMPONEN PERTUMBUHAN DAN HASIL, SERTA KUALITAS AROMA TIGA VARIETAS LOKAL PADI GOGO AROMATIK ASAL SUMBA BARAT DAYA TERHADAP TINGKAT KELEMBABAN TANAH - IGB Adwita Arsa (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2020)
Aroma quality of rice in addition to determined by genetic factor is also influenced by environmental factors. One of those that significantly affected the aroma quality of aromatic upland rice is soil moisture. The stronger fragrant aroma of rice often occurs at relatively low soil moisture level, so that the grain obtained relatively low, So that when the aroma quality of rice increases, the grain yield is lower. The purpose of this research is to know the influence of soil moisture to both growth and yield components, yield as well as the aroma quality of three local varieties of aromatic upland rice from South West Sumba. The experiment was carried out factorially in a split-plot design with three replications. The first factor was the level of soil moisture with four levels, namely: 100%, 80%, 60% and 40% FC and the second factor was local varieties, namely: Lapale Kuhi, Kiku Lapale, and Panenggo. The observed variables included: vegetative and reproductive characters, physiological characters and aroma quality. The data collected were analyzed by analysis of variance followed by the Honestly Significant Difference (HSD) Test at a 5% significance level. The results showed that: 1) Yield components and grain yield were the highest at 100% Field Capacity (FC) soil moisture level, and they were significantly lower at 40% FC soil moisture level, 2) Soil moisture level also significantly affected physiological characters, namely: N, Na, proline contents , and aroma quality of rice, 3) Decreasing the level of soil moisture reduces N content of leaves tissue, increases Na and proline contents of leaves tissue. Aroma score of rice increased with a decrease in soil moisture level, whereas 2-AP compound content of rice increased at soil moisture level 80 % FC and reduced both at 60% FC and 40% FC..